Trends of Diphtheria, Pertussis and Tetanus Cases in Nepal - Jha, N; Niraula, SR; Biral, DD; Bohara, R (Health Renaissance, 2013)
Health Renaissance, January-April 2013; Vol. 11 No.1; 47-53 DOI: http://dx.doi.org/10.3126/hren.v11i1.7602